INTEGRASI FILOSOFI PENDIDIKAN DAN TEORI MANAJEMEN DALAM PRAKTIK MANAJERIAL DI SDN 068 INP MARANNU - Mutmainnah; Suardi; Idawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Educational management at the elementary school level plays a crucial role in improving the quality of learning. A major issue encountered is the lack of optimal integration between educational philosophical values and management theories in school practices. This study aims to analyze the integration of humanism, essentialism, and progressivism with educational management theories in elementary school management practices. The research employed a descriptive qualitative approach conducted at SDN 068 INP Marannu, involving the principal and teachers as research subjects. Data were collected through interviews, observations, documentation, and questionnaires, and analyzed using source and technique triangulation. The findings indicate that humanistic values serve as the foundation for school policy-making, management functions based on POAC and the Internal Quality Assurance System (SPMI) are implemented adaptively, and stakeholder collaboration operates effectively. In conclusion, school management practices have contextually integrated educational philosophy and management theories to support the improvement of learning quality in elementary schools.